Central African Republic : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper describes economic developments in the Central African Republic during 1990-97. After four years of decline, the real gross domestic product of the Central African Republic (GDP at market prices) recovered in 1994 at the estimated rate of 7.7 percent. This primarily reflected the positive effects of the January 1994 devaluation of the CFA franc on the competitive position of the country, which had been continuously eroding since the mid-1980s. In 1995, real GDP continued to grow, although at a slower rate, estimated at 2.4 percent, largely because of the resilient informal sector.